PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBASIS ENVIRONMENT LEARNING UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH PADA SISWA SMA (IPF: Inovasi Pendidikan Fisika, 2022)
Learning Problem Based Learning (PBL) on Environment Learning is a learning model in which it relates material to the environment. This study aims to determine the improvement of problem solving abilities in high school students by using the Environmental Learning-based Problem Based Learning (PBL) model. This study uses a quasi-experimental method with a one group pretest-posttest design. This research procedure uses learning instrument validation and analyzes research data using the SPSS application. The conclusion of this research is that learning using the Problem Based Learning (PBL) learning model based on Environment Learning has increased the problem solving ability of students compared to using conventional learning models. Student responses in learning Environment Learning-based Problem Based Learning (PBL) are also positive and make learning more interesting and easy to understand compared to using conventional learning models. Keywords: Learning model Problem Based Learning based on Environment Learning, problem solving ability of students